Histological analysis of ACL reconstruction failures due to synthetic-ACL (LARS) ruptures - Di Benedetto, Paolo; Giardini, Piero; Beltrame, Alessandro; Mancuso, Francesco; Gisonni, Renato; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Anterior Cruciate Ligament (ACL) reconstruction is an established surgical procedure. Synthetic ligaments represent an option for ACL reconstruction. Their popularity declined for the raising concerns due to re-ruptures, knee synovitis and early arthritis related to I and II generation artificial ligaments. The introduction of a III generation synthetic ligament (Ligament Advanced Reinforcement System-LARS) permitted renewed interest in the adoption of this kind of graft. Main purpose of our study was to describe the histological findings on samples obtained from a consecutive series of ACL revision surgeries due to LARS ACL reconstruction failures. Secondary aim was to determine the reason for LARS rupture. Methods: In a period between 2016 and 2018 eleven patients underwent ACL revision surgery due to LARS ACL reconstruction failure. At the time of the arthroscopic procedure, samples of synovial membrane and remnants of the torn LARS were sent to the Pathological-Anatomy Institute of our Hospital for a histological analysis. Results: Histological analysis of the synovial tissues confirmed the arthroscopic evidence of synovitis mainly characterized by chronic inflammation with predominance of multinucleated giant cells. The adoption of polarized light microscopy revealed the presence of brightly bi-refractive material (LARS wear particles) in the synovial tissue; at higher magnification wear debris were detected inside the cytoplasma of multi nucleated cells. The histological analysis of the removed LARS revealed a surrounding typical foreign body reaction with poor signs of fibrovascular ingrowth of the synthetic ligament. Conclusions: Our findings could not clearly advocate a unique mechanism of LARS-ACL reconstruction failure: biologic issues (poor tissue ingrowth) and mechanical issues (fibers properties and tunnel position) probably concur in a multi factorial manner. ACL reconstruction using artificial ligaments can not be considered a simple surgery. Artificial augments require some expertise and could therefore achieve better results if used by skilled sport surgeons other than trainees or low volume surgeons. The Authors believe that ACL reconstruction with synthetic devices still have restricted indications for selected patients (e.g. elderly patients who require a fast recovery, professional athlete, autologous tendons not available and/or refusing donor tendons). Our study arises additional suspicion on the unresponsiveness of synthetic fibers and claim some concern in the implantation of synthetic devices.